Lodgers in the house: living with the data in interpretive phenomenological analysis research. Issue 1 (2nd January 2020) - Engward, Hilary; Goldspink, Sally
ABSTRACT: This paper provides a practical analysis of being reflexive when doing Interpretive Phenomenological Analysis (IPA) research. We argue that although reflexivity is widely discussed in relation to qualitative research, there are few practical examples demonstrating how to be reflexive. To address this, reflexivity will be presented through the experiences learnt from doctoral research using IPA. Reflexivity is understood in qualitative research as an attentiveness to the influence of the researcher on the research process.. However, experiencing reflexivity as an IPA researcher is tricky, time-consuming and often uncomfortable; it does not 'happen' and the researcher had to learn to 'live' with data. Drawing on the work of Heidegger, the experience and expression of reflexivity is conceptualised as the 'house of being', a shared analytic space that researchers and participants inhabit. This paper adds to the existing discussion of reflexivity by extending the dialogue of 'what is it like' to be reflexive and how to integrate reflexivity into research. The insights in this paper are intended to generate insight as to how reflexivity can be overt in the doing and writing of IPA research and to assist IPA and qualitaive researchers in their awareness and implementation of reflexivity in research .